SINTESIS KARBON BERPORI BERBASIS DAUN JERUK NIPIS (Citrus Aurentifolia S.) SEBAGAI MATERIAL ELEKTRODA UNTUK APLIKASI SUPERKAPASITOR - Erman Taer; Melda Riyani Butet; Apriwandi Apriwandi; Rika Taslim (Universitas Riau, 2023)
In this study, the electrode material was successfully made from activated carbon based on lime leaf biomass with variations in physical activation temperature of 800 ˚C, 850 ˚C, and 900 ˚C for supercapacitor applications. Porous carbon was synthesized through pre-carbonization steps, chemical activation using ZnCl2 activator, carbonization using N2 gas at a temperature of 600 ˚C, and physical activation using CO2. Density analysis confirmed the potential for the DJN-850 sample to have a high shrinkage of 52.24%. X-ray diffraction shows an amorphous structure of carbon characterized by broading peaks at 2θ=22° and 24°. Scanning electron microscopy analysis performed that the optimized sample possessed rich meso-,macropores followed by a high carbon content of 90.25%. The Fourier spectroscopic transformation test results identified the presence of functional groups O-H, C-O, C-H, C=C, and C≡C in the sample. The precursor activated at 850 C possessed a specific surface area of 675.129 m2 g-1 with adjusting micro-mesopore. Furthermore, the electrochemical properties of the samples were measured using cyclic voltammetry and galvanostatic charge-discharge with specific capacitances of 144.14 F g-1 and 189 F g-1, respectively.. Keywords: biomass precursor; Citrus aurentifolia S., carbon porous, electrode material, supercapacitor